2008
DOI: 10.1111/j.1745-7254.2008.00716.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic preconditioning attenuates hypoxia/reoxygenation-induced apoptosis in mesenchymal stem cells

Abstract: Aim: Mesenchymal stem cells (MSC) are a promising candidate for cardiac replacement therapies. However, the majority of transplanted MSC are readily lost after transplantation because of poor blood supply, ischemia-reperfusion, and inflammatory factors. We aimed to study the effects of hypoxia preconditioning (HPC) on hypoxia/reoxygenation-induced apoptosis of MSC. Methods:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
93
1
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(98 citation statements)
references
References 24 publications
0
93
1
4
Order By: Relevance
“…Кардиологи из Китая [53] воспроизводили ГП, по-мещая МСК на 10, 20 или 30 минут в газовую среду, содержащую 8% О 2 , с последующей реоксигенацией пе-ред моделирова нием длительной гипоксии (6 ч, 5% О 2 ) и реоксигенацией (12 ч). При оценке выживаемости МСК и количества апоптозных (TUNEL-позитивных) клеток оказалось, что все три типа ГП в равной мере по-вышали выживаемость МСК, а наиболее выраженный анти апоптозный эффект оказывала гипоксия продол-жительностью 30 минут.…”
Section: актуальные вопросы патофизиологииunclassified
See 3 more Smart Citations
“…Кардиологи из Китая [53] воспроизводили ГП, по-мещая МСК на 10, 20 или 30 минут в газовую среду, содержащую 8% О 2 , с последующей реоксигенацией пе-ред моделирова нием длительной гипоксии (6 ч, 5% О 2 ) и реоксигенацией (12 ч). При оценке выживаемости МСК и количества апоптозных (TUNEL-позитивных) клеток оказалось, что все три типа ГП в равной мере по-вышали выживаемость МСК, а наиболее выраженный анти апоптозный эффект оказывала гипоксия продол-жительностью 30 минут.…”
Section: актуальные вопросы патофизиологииunclassified
“…Последняя катализирует превращение прокаспазы-3 в каспазу-3, что в конечном итоге ведет к апоптозу [54]. Очевидно, что способность белка Bcl-2 препятствовать открытию МРТ-поры объясняет тот факт, что в прекон-диционированных МСК сохраняется высокий потенциал на внутренней мембране митохондрий (∆ψ), и снижается интенсивность апоптоза [53]. Кроме того, авторы об-наружили, что ГП вызывает фосфорилирование киназ ERK (extracellular regulated kinase) и Akt [53].…”
Section: актуальные вопросы патофизиологииunclassified
See 2 more Smart Citations
“…[14][15][16][17] Several in vitro studies have been reported that HIF is a powerful factor, which improved survival and differentiation of stem cells. 18,19 In particular, HIF-1 caused resistance to chemotherapy and radiation approaches. 20 Here, we investigated the effects of Umbilical cord blood-derived mesenchymal stem cells (UCB-MSCs) on proliferation rate, cell death and some genes expression by U937 cells in hypoxia milieu.…”
Section: Introductionmentioning
confidence: 99%